Empowerment Communication Strategy Based on Local Wisdom at Nggruput Tourism in Pringsewu Regency Lampung - Prastiwi, Herliana; Nasor, M; Badi’ah, Siti; Yanti, Fitri (Journal of Community Service and Empowerment, 2026)
Empowerment, from a social science perspective, is defined as an effort to meet the needs required by an individual or community group. Community participation plays a crucial role in making empowerment a process that creates a conducive environment for developing the potential of the people. For the empowerment process to run effectively, there must be efforts to raise community awareness about the conditions they face through communication strategies. Pringsewu Regency possesses local potential, resources, and natural beauty that have been utilized by the Nggruput Pringsewu Community, the initiators of the Sunday Morning Market tourism program, known as Nggruput Pringsewu. This traditional market significantly supports the economic growth of the Pringsewu area. This research aims to analyze the communication strategies employed by the Nggruput Pringsewu Community and the outcomes of community empowerment through the Nggruput tourism initiative in Pringsewu Regency. The research uses a qualitative field study approach. Data were collected through observation, interviews, and documentation. The data analysis was conducted through three stages: data reduction, data presentation, and conclusion drawing or verification. The findings indicate that: 1) The communication strategy applied by the Nggruput Pringsewu Community in empowering the community is based on participatory principles. The strategy is implemented through three main approaches: community participation, the use of digital technology, and collaboration with various stakeholders including the government, social communities, and youth organizations (Karang Taruna). 2) The results of community empowerment through Nggruput tourism are evident in two main aspects: social and economic. In the social aspect, there is an improvement in community well-being through active involvement in tourism management, the development of public facilities, and social and educational activities conducted by the community. In the economic aspect, the Nggruput tourism initiative creates business opportunities for the community, thus increasing local incomes.